Analysis of A Mid Rise Structure Considering Construction Sequence Analysis for RCC Structure Using ETABS A Review - Shrikant Nema; Singhai, Rahul Satbhaya (International Journal of Scientific Research in Civil Engineering, 2024)
While analyzing a multistorey building frame, conventionally all the probable loads are applied after modeling the entire building frame. But in practice the frame is constructed in various stages. Accordingly, the stability of frame varies at every construction stage. Even during construction freshly placed concrete floor is supported by previously cast floor by formwork. In this project two cases have been considered. In Case 1 the multistoried building (G+4 storied) was analyzed by response spectrum method and considering P-delta effect as a whole for the subjected loading and in Case 2 the multistoried building (G+4 storied) was analyzed by response spectrum method with reference to the construction sequence or staged construction and considering P-delta effect. In the present study a G+4 storey multistoried R.C.C building model is modelled using Etabs 2018 software.
Keywords: Construction Sequence Analysis; P-delta effect; Response Spectrum Analysis; Etabs software